Non-tidal loading by the Baltic Sea: Comparison of modelled deformation with GNSS time series. (September 2015) - Nordman, M.; Virtanen, H.; Nyberg, S.; Mäkinen, J.
Abstract: We study the influence of non-tidal loading by the Baltic Sea on GNSS daily coordinate time series. The momentary sea surface is estimated from hourly tide gauge recordings around the Baltic and the load is convolved with Green's functions to determine 3-D deformation, gravity, potential and tilt effects at 193 stations around the Baltic. This paper concentrates on 3-D deformation at a small number of continuous GNSS stations. Daily coordinate time series based on both Precise Point Positioning (PPP) and double differences (DD) were used. We find that for the east component of inter-station vectors crossing the Baltic, up to 56% of the variance can be explained by the Baltic loading. In the north and up components the Baltic loading is not well detectable. We think that for the north component this is due to station positions, and for the up component also to interaction with regional atmospheric loading.